Significance of changes in endurance shuttle walking performance. Issue 2 (8th December 2010) - Pepin, Véronique; Laviolette, Louis; Brouillard, Cynthia; Sewell, Louise; Singh, Sally J; Revill, Sue M; Lacasse, Yves; Maltais, François
Abstract : Background: The endurance shuttle walking test (ESWT) has shown good responsiveness to interventions in patients with chronic obstructive pulmonary disease (COPD). However, the minimal important difference (MID) for this test remains unknown, therefore limiting its interpretability. Methods: Patients with COPD who completed two or more ESWTs following pulmonary rehabilitation (n=132; forced expiratory volume in 1 s (FEV1 ) 48±22%) or bronchodilation (n=69; FEV1 50±12%) rated their performance of the day in comparison with their previous performance on a 7-point scale ranging from −3 (large deterioration) to +3 (large improvement). The relationship between subjective perception of changes and objective changes in performance during the shuttle walk was evaluated. Results: Following pulmonary rehabilitation, the anchor-based approach did not allow a valid estimation of the MID in the ESWT performance to be obtained. After bronchodilation, patient ratings of change correlated significantly with the difference in walking distance (r=0.53, p<0.001) and endurance time (r=0.55, p<0.001). For the pharmacotherapy data, regression analysis indicated that a 65 s (95% CI 45 to 85) change in endurance time and a 95 m (95% CI 60 to 115) change in walking distance were associated with a 1-point change in the rating of change scale. These changes represented 13–15% of the baseline values. Conclusions: A change in endurance shuttle walking performance of 45–85 s (or 60–115 m) after bronchodilation is likely to be perceived by patients. This MID value may be specific to the intervention from which it was derived.